A polysaccharide of PFP-1 from Pleurotus geesteranus attenuates alcoholic liver diseases via Nrf2 and NF-κB signaling pathways. Issue 10 (28th April 2021) - Song, Xinling; Sun, Wenxue; Cui, Weijun; Jia, Le; Zhang, Jianjun
Abstract : A polysaccharide named PFP-1 was isolated from the Pleurotus geesteranus fruiting body, and potential investigations on ameliorating oxidative stress and liver injury against alcoholic liver disease (ALD) were performed in mice. Abstract : A polysaccharide named PFP-1 was isolated from the Pleurotus geesteranus fruiting body, and potential investigations on ameliorating oxidative stress and liver injury against alcoholic liver disease (ALD) were performed in mice. The animal studies demonstrated that PFP-1 had hepatoprotective effects by improving hepatocellular histopathology, modulating alcohol metabolisms and restoring the serum lipid levels. Besides, PFP-1 could attenuate oxidative stress and inflammatory responses by activating the Nrf2-mediated signal pathways and regulating the TLR4-mediated NF-κB signal pathways. The characterization indicated that PFP-1 was a typical pyranose-polysaccharide in a triple-helical conformation, which was linked by t-β-Glc p, 1, 6-α-Glc p and 1, 2, 6-α-Gal p . And the characteristic properties of higher water solubility and appropriate molecular weights contributed to the superior bioactivities. The results demonstrated that PFP-1 could be used as a supplement for alleviating alcohol-induced liver damage.